Regeneration of a Former Prison in Melipilla, Chile: Use of Digital Technology in a Heritage Restoration Project - Atria-Lannefranque, J; Correa-Baeriswyl, M (European Council on Computing in Construction (EC3), 2023)
Technology and automation in the field of cultural heritage provide an opportunity for the restoration of historical buildings that would otherwise remain abandoned and overlooked amid the current development of cities in Latin America. The present paper proposes the restoration and regeneration project to transform an abandoned former prison in the city of Melipilla, Chile, into a public library, upgrading and opening its spaces to the public and making contemporary use of this crumbling landmark that has a high potential of social renovation. The case study is the repurposing of a building of considerable cultural interest, neglected in an historical central urban tissue, by creating a new function and demonstrating the feasibility of upgrading an older structure to comply with current parameters of indoor environmental quality (IEQ) (i.e. light intensity and thermal comfort) through the appropriate use of passive energy controlled by means of a digital twin approach and automation of adaptive measures. © 2023, European Council on Computing in Construction (EC3). All rights reserved.